2017
DOI: 10.1111/gtc.12510
|View full text |Cite
|
Sign up to set email alerts
|

NGL‐3‐induced presynaptic differentiation of hippocampal neurons in an afadin‐dependent, nectin‐1‐independent manner

Abstract: A hippocampal mossy fiber synapse, which is implicated in learning and memory, has a complex structure. We have previously shown using afadin-deficient mice that afadin plays multiple roles in the structural and functional differentiations of this synapse. We investigated here using a co-culture system with cultured hippocampal neurons and non-neuronal COS-7 cells expressing synaptogenic cell adhesion molecules (CAMs) whether afadin is involved in the presynaptic differentiation of hippocampal synapses. Postsy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 44 publications
(97 reference statements)
0
6
0
Order By: Relevance
“…-Catenin, also known as junction plakoglobin, is a protein homologous to -catenin, but is localized at desmosomes in various types of cells including epithelial cells and associates desmosomal cadherins with the intermediate filament cytoskeleton through desmoplakin (Delva et al, 2009), but its role in synapses remains unknown. We have not investigated here the physiological functions of the binding of -catenin to s-afadin, but the present results raised the possibility that -catenin and its binding to s-afadin regulate the formation of the synaptic junctions, because it was previously shown that s-afadin is localized at the synaptic junctions (Maruo et al, 2017;Nishioka et al, 2000). The lysates from HEK293 cells expressing FLAG-tagged EGFP, FLAG-tagged l-afadin, or FLAG-tagged s-afadin with -catenin were immunoprecipitated with the anti-FLAG M2 mAb.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…-Catenin, also known as junction plakoglobin, is a protein homologous to -catenin, but is localized at desmosomes in various types of cells including epithelial cells and associates desmosomal cadherins with the intermediate filament cytoskeleton through desmoplakin (Delva et al, 2009), but its role in synapses remains unknown. We have not investigated here the physiological functions of the binding of -catenin to s-afadin, but the present results raised the possibility that -catenin and its binding to s-afadin regulate the formation of the synaptic junctions, because it was previously shown that s-afadin is localized at the synaptic junctions (Maruo et al, 2017;Nishioka et al, 2000). The lysates from HEK293 cells expressing FLAG-tagged EGFP, FLAG-tagged l-afadin, or FLAG-tagged s-afadin with -catenin were immunoprecipitated with the anti-FLAG M2 mAb.…”
Section: Discussionmentioning
confidence: 74%
“…We therefore next examined why s-afadin was unable to show this activity. In the preceding paper, we prepared the lysate of the light membrane fraction of mouse brain and examined which proteins are co-immunoprecipitated from this lysate with the anti-l-afadin Ab, which recognizes l-afadin, but not s-afadin, and the anti-l/s-afadin Ab, which recognizes both l-afadin and s-afadin (Maruo et al, 2017). We presented the Western blotting data in that paper showing that nectin-1, nectin-3, -catenin, and 2-catenin were co-immunoprecipitated with both l-afadin and s-afadin, and that -catenin was co-immunoprecipitated with s-afadin, but faintly with l-afadin.…”
Section: Binding Of -Catenin To S-afadin But Not To L-afadin and Binding Of N-catenin To L-afadin But Not To S-afadinmentioning
confidence: 99%
“…S5, D–F). This group included genes from all of the three protocadherin clusters on chromosome 5 (α, β, and γ, exemplified by PCDHA10 , PCDHB15 , and PCHDGB4 ; Chen and Maniatis, 2013 ), LRRC4B (encoding for the postsynaptic cell adhesion molecule NGL-3; Maruo et al, 2017 ), SYT3 (involved in postsynaptic endocytosis; Awasthi et al, 2018 ), and CACNA1A (which encodes for the pore-forming subunit of neuronal P/Q-type calcium channels; Rajakulendran et al, 2012 ).…”
Section: Resultsmentioning
confidence: 99%
“…We previously showed that l-afadin and s-afadin are mainly localized at the PAJs and partly at the SJs ( 8 ). The three-dimensional structure of the afadin -deficient hippocampal mossy fiber synapses showed that afadin was required for the AZ formation, assembly of the docked synaptic vesicles and synaptic vesicles in the readily releasable pool, and arborization of the postsynaptic spines ( 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the hippocampal mossy fiber synapse PAJs, l-afadin as well as N-cadherin and αN-catenin is symmetrically localized at the presynaptic and postsynaptic sides, whereas nectin-1 and nectin-3 are asymmetrically localized at the presynaptic and postsynaptic sides, respectively ( 6 , 7 ). In addition to this localization, l-afadin and presumably s-afadin are localized partly at the SJs in the dendritic spines ( 8 , 9 , 10 ). Our recent studies on the in vivo and in vitro roles of afadin in the structural and functional differentiations of the hippocampal synapses showed that the localization of nectin-1, nectin-3, and N-cadherin is impaired in the afadin -deficient synapses.…”
mentioning
confidence: 95%